Wyznacz w(X) + P(X) , w(X) -P(X), w (X)x P(X) jeśli w(X)= -3x²-7x+1 i
P(X)= x³=2x²-3



Odpowiedź :

Wyznacz w(X) + P(X) , w(X) -P(X), w (X)x P(X) jeśli

w(X)= -3x²-7x+1 i
P(X)= x³=2x²-3 Pytaniem czy tu ma być znak "+" czy znak "=". Założę, że ten pierwszy ;p

w(x) + p(x) = (-3x²-7x+1)+(x³+2x²-3)=-3x²-7x+1+x³+2x²-3 =
= x³-2x²-7x-2

w(x) -p(x)=(-3x²-7x+1)-(x³+2x²-3)=-3x²-7x+1- x³-2x²+3=-x³-5x²-7x+4

w(x)*p(x) = (-3x²-7x+1)+(x³+2x²-3)= -3x⁵ -6x⁴+9x²-7x⁴ -14x³+21x +x³ +2x² -3= -3x⁵ -13x⁴-13x³+11x²-21x-3